2020
DOI: 10.1186/s12887-020-02344-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of congenital heart disease on outcomes among pediatric patients hospitalized for influenza infection

Abstract: Background Young children and those with chronic medical conditions are at risk for complications of influenza including cardiopulmonary compromise. Here we aim to examine risks of mortality, clinical complications in children with congenital heart disease (CHD) hospitalized for influenza. Methods We analyzed data from in-hospital pediatric patients from 2003, 2006, 2009, 2012 and 2016 using the nationally representative Kids Inpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Numerous studies have indicated that viral respiratory infections, including influenza and COVID-19, impose a higher risk of mortality, a longer duration of hospitalization, and more complications and economic costs in patients with CHD than the general population [6,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that viral respiratory infections, including influenza and COVID-19, impose a higher risk of mortality, a longer duration of hospitalization, and more complications and economic costs in patients with CHD than the general population [6,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies reported increased complications in influenza infections associated with heart disease [ 18 , 19 ]. Although it is more common in adults, children with heart disease who are admitted to the hospital for influenza are at an increased risk for severe outcomes, such as in-hospital mortality and morbidities [ 20 ]. Unsurprisingly, children with hematologic disorders and other immune-suppression disorders were also more prone to experience severe influenza symptoms and be admitted, while children with psychiatric disorders experienced a longer length of hospital stay [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…21 When admitted to the hospital for influenza, such children are at significantly increased risk for in-hospital mortality, acute respiratory failure, acute kidney injury, need for invasive and noninvasive mechanical ventilation, myocarditis, and need for extracorporeal membrane oxygenation. 22 Understandably, this corresponded with a higher length of stay. 22 These complications were found to be independent of the severity of the CHD, indicating that children and adolescents with mild or moderate heart defects also benefit from vaccination.…”
Section: Discussionmentioning
confidence: 95%
“…22 Understandably, this corresponded with a higher length of stay. 22 These complications were found to be independent of the severity of the CHD, indicating that children and adolescents with mild or moderate heart defects also benefit from vaccination. 22 The predictors for vaccination were the complexity of the heart defect, a higher age, genetic syndromes, and a history of cardiac interventions.…”
Section: Discussionmentioning
confidence: 95%